Hypocalcemia in trauma patients: A systematic review. Issue 2 (February 2021) - Vasudeva, Mayank; Mathew, Joseph K.; Groombridge, Christopher; Tee, Jin W.; Johnny, Cecil S.; Maini, Amit; Fitzgerald, Mark C.
Abstract : BACKGROUND: During hemorrhagic shock and subsequent resuscitation, pathways reliant upon calcium such as platelet function, intrinsic and extrinsic hemostasis, and cardiac contractility are disrupted. The objective of this systematic review was to examine current literature for associations between pretransfusion, admission ionized hypocalcemia, and composite outcomes including mortality, blood transfusion requirements, and coagulopathy in adult trauma patients. METHODS: This review was reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist. We searched Ovid MEDLINE and grey literature from database inception till May 3, 2020. Case series and reports were excluded. Reference lists of appraised studies were also screened for articles that the aforementioned databases might not have captured. The Newcastle-Ottawa Scale was used to assess study quality. RESULTS: A total of 585 abstracts were screened through database searching and alternative sources. Six unique full-text studies were reviewed, of which three were excluded. Admission ionized hypocalcemia was present in up to 56.2% of the population in studies included in this review. Admission ionized hypocalcemia was also associated with increased mortality in all three studies, with increased blood transfusion requirements in two studies, and with coagulopathy in one study. CONCLUSION: Hypocalcemia is a common finding in shocked trauma patients. While an association between admission ionized hypocalcemia and mortality, blood transfusion requirements, and coagulopathy has been identified, further prospective trials are essential to corroborating this association. LEVEL OF EVIDENCE: Systematic review, level III. Abstract : Supplemental digital content is available in the text.